2012
DOI: 10.1089/dia.2012.0170
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of a New 32-Gauge×4-mm Pen Needle and a 32-Gauge×6-mm Pen Needle on Glycemic Control, Safety, and Patient Ratings in Japanese Adults with Diabetes

Abstract: The 32-gauge × 4-mm PN was not only as safe and efficacious as the 32-gauge × 6-mm PN, but also was perceived as less painful, easier to use, and more favorable to Japanese adult patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 20 publications
1
26
0
3
Order By: Relevance
“…12 Prospective, controlled trials (mostly crossover studies) comparing different length needles have consistently found equivalent glycemic control, less pain, and minimal ''backflow'' or skin leakage with shorter lengths, which patients usually prefer. 8,9,[15][16][17][18][19] A randomized, controlled study confirmed these outcomes for a 4 mm · 32 gauge pen needle, versus 5 mm and 8 mm · 31 gauge needles, in adults with diabetes and BMI up to 49 kg/m 2 ; a post hoc analysis showed equivalent glycemic control without increased skin leakage for the 4 mm needle in the obese subjects, similar to the nonobese ones. 16,20 A prospective randomized, controlled crossover study in obese patients (BMI up to 60 kg/m 2 ) has been reported and confirms such findings for the 4 mm-length needle compared with both 8 mm-and 12.7 mm-length needles.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…12 Prospective, controlled trials (mostly crossover studies) comparing different length needles have consistently found equivalent glycemic control, less pain, and minimal ''backflow'' or skin leakage with shorter lengths, which patients usually prefer. 8,9,[15][16][17][18][19] A randomized, controlled study confirmed these outcomes for a 4 mm · 32 gauge pen needle, versus 5 mm and 8 mm · 31 gauge needles, in adults with diabetes and BMI up to 49 kg/m 2 ; a post hoc analysis showed equivalent glycemic control without increased skin leakage for the 4 mm needle in the obese subjects, similar to the nonobese ones. 16,20 A prospective randomized, controlled crossover study in obese patients (BMI up to 60 kg/m 2 ) has been reported and confirms such findings for the 4 mm-length needle compared with both 8 mm-and 12.7 mm-length needles.…”
Section: Discussionmentioning
confidence: 75%
“…Most patients using needles ‡ 6 mm in length must either inject at an angle and/or raise a skinfold (''pinch-up'') to effectively reduce IM risk; 4 and 5 mm pen needles are a safe and equally effective alternative. 12,[15][16][17][18][19] The persistent use of 8-12.7 mm needles for insulin therapy appears to be based on habit and clinical inertia, without any evidence of superior metabolic control or reduction in injection problems, such as leakage or backflow from the skin. 8,12,15,16,19 Such needles are longer than is necessary for consistent SC drug delivery and offer no inherent advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Miwa et al [26] compared 4-mm/32G with 6-mm/32G needles and showed equivalent safety and efficacy results. The 4-mm needle was judged by Japanese patients to be less painful and easier to use.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have recently been done in Asia with the 4-mm needle and have yielded comparable results. Miwa et al [9] compared 4-mm with 6-mm needles in Japanese patients, and showed similarly safe and efficacious results. The 4-mm needle was also adjudged less painful and easier to use.…”
Section: Discussionmentioning
confidence: 97%